Long-Term Survival Analysis of Korean Breast Cancer Patients at a Single Center: Improving Outcome Over Time - Ahn, Sung Gwe; Lee, Hak Min; Lee, Seung Ah; Jeong, Joon; Lee, Hy-De (Yonsei medical journal, 2014)
The prognosis of breast cancer has been consistently improving. We analyzed our cohort of breast cancer patients with a long-term follow up at a single center over time. A total of 1889 patients with known cancer stages were recruited and analyzed between January 1991 and December 2005. Patients were classified according to the time periods (1991-1995; 1996-2000; 2001-2005). To determine intrinsic subtypes, 858 patients whose human epidermal growth receptor-2 status and Ki67 were reported between April 2004 and December 2008 were also analyzed. At a median follow up of 9.1 years, the 10-year overall survival (OS) rate was 80.5% for the entire cohort. On multivariate analysis for OS and recurrence-free survival (RFS), the time period was demonstrated to be a significant factor independent of conventional prognostic markers. In the survival analysis performed for each stage (I to III), OS and RFS significantly improved according to the time periods. Adoption of new agents in adjuvant chemotherapy and endocrine therapy was increased according to the elapsed time. In the patients with known subtypes, OS and RFS significantly differed among the subtypes, and the triple-negative subtype showed the worst outcome in stages II and III. In the Korean breast cancer cohort with a long-term follow up, our data show an improved prognosis over the past decades, and harbor the contribution of advances in adjuvant treatment. Moreover, we provided new insight regarding comparison of the prognostic impact between the tumor burden and subtypes.